Australian journal of adult and community education. - Australian Association of Adult and Community Education (Underdale, South Australia : Australian Association of Adult and Community Education, 1990)
Journal provides information and analysis on theory, research and practice of adult and community education; includes topic Aboriginal education.
Title from cover.
Australian education index
Educational administration abstracts
Available on microfilm from University Microfilms, Ann Arbor, MI.
ISSN registration
Keywords: Adult education -- Australia -- Periodicals; Community education -- Australia -- Periodicals; Community organisations - Education; Education - Adult education; Australia; Australian